Gingival recession: its causes and types, and the importance of orthodontic treatment - Ana Suzy Jati; Laurindo Zanco Furquim; Alberto Consolaro
abstract Gingival recession has direct causes and predisposing factors. Orthodontic treatment is able to prevent recession and even contribute to its treatment, with or without periodontal approach, depending on the type and severity of gingival tissue damage. There is no evidence on the fact that orthodontic treatment alone might induce gingival recession, although it might lead the affected teeth (usually mandibular incisors or maxillary canines) to be involved in situations that act as predisposing factors, allowing direct causes to act and, therefore, trigger recession, especially when the buccal bone plate is very thin or presents with dehiscence. Several aspects regarding the relationship between orthodontic treatment and gingival recession have been addressed, and so has the importance of the periosteum to the mechanism of gingival recession formation. Clinical as well as experimental trials on the subject would help to clarify this matter, of which understanding is not very deep in the related literature.